A Novel Design of Multi-Chambered Biomass Battery - Sudhakar, K.; Ananthakrishnan, R.; Goyal, A.; Darji, H.K. (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
In this paper, a novel design of biomass battery has been introduced for providingelectricity to meet the lighting requirements of rural household using biomass. A biomass battery isdesigned, developed and tested using cow dung as the raw material. This is done via anaerobicdigestion of the cow dung, and power generation driven by the ions produced henceforth. Thevoltage and power output is estimated for the proposed system. It is for the first time that such ahigh voltage is obtained from cow dung fed biomass battery. The output characteristics of thisnovel battery design have also been compared with the previously designed battery.